Dynamic functions of GABA signaling during granule cell maturation - Dieni, Cristina V.; Chancey, Jessica H.; Overstreet-Wadiche, Linda S. (Frontiers in Neural Circuits, 2013)
The dentate gyrus is one of the few areas of the brain where new neurons are generated throughout life. Neural activity influences multiple stages of neurogenesis, thereby allowing experience to regulate the production of new neurons. It is now well established that GABAA receptor-mediated signaling plays a pivotal role in mediating activity-dependent regulation of adult neurogenesis. GABA first acts as a trophic signal that depolarizes progenitors and early post mitotic granule cells, enabling network activity to control molecular cascades essential for proliferation, survival and growth. Following the development of glutamatergic synaptic inputs, GABA signaling switches from excitatory to inhibitory. Thereafter robust synaptic inhibition enforces low spiking probability of granule cells in response to cortical excitatory inputs and maintains the sparse activity patterns characteristic of this brain region. Here we review these dynamic functions of GABA across granule cell maturation, focusing on the potential role of specific interneuron circuits at progressive developmental stages. We further highlight questions that remain unanswered about GABA signaling in granule cell development and excitability.